2011
DOI: 10.1074/jbc.m110.171124
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Inhibits Protein Splicing, Suggesting Inteins as Therapeutic Targets in Mycobacteria

Abstract: Mycobacterium tuberculosis harbors three protein splicing elements, called inteins, in critical genes and their protein products. Post-translational removal of the inteins occurs autocatalytically and is required for function of the respective M. tuberculosis proteins. Inteins are therefore potential targets for antimycobacterial agents. In this work, we report that the splicing activity of the intein present in the RecA recombinase of M. tuberculosis is potently inhibited by the anticancer drug cisplatin (cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 41 publications
(27 reference statements)
1
56
1
Order By: Relevance
“…Appearance of multiand extensively drug-resistant strains of M. tuberculosis highlights the need for novel treatment options targeting different cellular processes (28,29). It was shown previously that the chemotherapeutic agent cisplatin is a potent intein inhibitor that arrests the growth of M. tuberculosis in a targeted fashion (14). Here, through testing of more Pt(II) compounds, we discovered that Pttfbz and Zeise's salt are of equivalent potency in vitro with IC 50 values in the 2 M range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Appearance of multiand extensively drug-resistant strains of M. tuberculosis highlights the need for novel treatment options targeting different cellular processes (28,29). It was shown previously that the chemotherapeutic agent cisplatin is a potent intein inhibitor that arrests the growth of M. tuberculosis in a targeted fashion (14). Here, through testing of more Pt(II) compounds, we discovered that Pttfbz and Zeise's salt are of equivalent potency in vitro with IC 50 values in the 2 M range.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the compounds was tested with a fluorescence-based assay using a split GFP construct (29 kDa) containing a minimized RecA intein (15.3 kDa) as described previously (14,19). Inhibition by the compounds was determined by fitting the data with a dose-response curve and calculating the inhibition constant, IC 50 ( Fig.…”
Section: Binding Of Platinum Compounds To Reca Intein Depends On the mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Asp118 is mutated to Gly in C * to confer C‐terminal cleavage activity in the absence of N‐terminal cleavage (Ramirez et al, ), and this protein as well as proteins lacking Cys + 1 (construct 5–23) also potently inhibited by Zn 2+ . In addition, we tested the ability of cisplatin, an inhibitor of the Rec A intein presumably through targeting the Cys1 (Zhang et al, ), can also inhibit C‐terminal of our intein at low micromolar concentration (data not shown). It is worth noting that our engineered intein has Cys1 mutated to Ala to abolish the first thio‐ester transfer step.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing splicing, and thus the maturation of non-functional precursor to functional spliced product presents a novel method of eliminating protein activity and suggests inteins as potential antimicrobial targets (Belfort 1998; Lew and Paulus 2002). Indeed, it has been shown that the potent in vitro intein inhibitor cisplatin kills M. tuberculosis in vivo (Zhang et al 2011). This effect relied upon the N-terminal catalytic cysteine residue of the intein.…”
Section: Biological Contextmentioning
confidence: 99%